2021
DOI: 10.3389/fnins.2021.642015
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular Nucleus Infusion of Oligomeric Proantho Cyanidins Improves Renovascular Hypertension

Abstract: Oxidative stress plays an important role in the pathogenesis of hypertension. Oligomeric proantho cyanidins (OPC) is the main polyphenol presents in grape seed and is known for its potent antioxidant and anti-inflammatory properties. In the present study, we hypothesize that OPC can attenuate oxidative stress in the paraventricular nucleus of hypothalamus (PVN), ameliorate neurotransmitter imbalance, decrease the blood pressure and sympathetic activity in renovascular hypertensive rats. After induction of reno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…In this experiment, two kidneys and one clip (2K1C) method was used to construct a hypertensive rat model as mentioned before ( Yu et al, 2021 ). Before the experiment, SD male rats were adaptively fed for 1 week, and blood pressure was tested.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this experiment, two kidneys and one clip (2K1C) method was used to construct a hypertensive rat model as mentioned before ( Yu et al, 2021 ). Before the experiment, SD male rats were adaptively fed for 1 week, and blood pressure was tested.…”
Section: Methodsmentioning
confidence: 99%
“…The systolic blood pressure (SBP) was detected using tail-cuff method every week as previously described ( Yu et al, 2021 ). Un-anesthetized rats were warmed to an ambient temperature of 32°C by placing rats in a holding device mounted on a thermostatically controlled warming plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported reactive oxygen species (ROS) production in the PVN, which induces abnormal sympathetic activity in the hypertensive rats [ 20 , 21 ]. ROS within the PVN was shown to play important roles in regulating RSNA in the ANG II or high salt-induced hypertension animal models [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamic paraventricular nucleus (PVN) regulates respiration, blood pressure (BP), and cardiovascular activity as an integrative element of the neuroendocrine and autonomic nervous systems (Rostami & Hatam, 2022;Xia et al, 2021;Yu et al, 2022). We and other research teams have previously demonstrated that reactive oxygen species (ROS) buildup and an unbalanced ratio of anti-to pro-in ammatory cytokines (PICs) in the PVN were shown to be associated with high blood pressure in hypertensive rats (Gao et al, 2021;Kang et al, 2019;Yu et al, 2021). The elevated sympathetic nervous system excitability may be signi cantly in uenced by high ROS and PICs levels in the PVN.…”
Section: Introductionmentioning
confidence: 99%